2015
DOI: 10.1055/s-0035-1566252
|View full text |Cite
|
Sign up to set email alerts
|

A New Window for the Treatment of Posterior Cerebral Artery, Superior Cerebellar Artery, and Basilar Apex Aneurysm: The Expanded Endoscopic Endonasal Approach

Abstract: The endoscopic endonasal transclival approach represents a potentially feasible surgical corridor to treat aneurysms arising from these vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The boxplot, and the significant improvement of reconstructive techniques have significantly extended the endoscopic option beyond the limits of the extradural compartments. In fact, the use of the EEEAs has recently been proposed for intradural lesions, such as meningiomas involving the ventral FM and the petroclival region (4,19,23,53), and ventrally located ponto-medullary cavernomas (12,18,27,36,44,51), or even aneurysms of the vertebrobasilar system (14,26,45,48,49). Due to the lower rate of infection or functional complications with the use of EEEAs, such approaches are more preferred than purely microscopic or endoscope-assisted transoral approaches (7).…”
Section: Dimensional Variability Of the Condylar And Basilar Partmentioning
confidence: 99%
“…The boxplot, and the significant improvement of reconstructive techniques have significantly extended the endoscopic option beyond the limits of the extradural compartments. In fact, the use of the EEEAs has recently been proposed for intradural lesions, such as meningiomas involving the ventral FM and the petroclival region (4,19,23,53), and ventrally located ponto-medullary cavernomas (12,18,27,36,44,51), or even aneurysms of the vertebrobasilar system (14,26,45,48,49). Due to the lower rate of infection or functional complications with the use of EEEAs, such approaches are more preferred than purely microscopic or endoscope-assisted transoral approaches (7).…”
Section: Dimensional Variability Of the Condylar And Basilar Partmentioning
confidence: 99%
“…There are also some literature reports on the cadaver study using the EEA for clipping intracranial aneurysms. [30][31][32][33][34][35][36][37][38][39][40][41] Many previous articles on cadaver studies have suggested that ACoA aneurysms can be clipped through the EEA, but Montaser et al 32 did not fully agree. To further analyze the clipping of ACoA aneurysms by this approach, we first simulated the approach with a cadaver head.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning a relatively new approach for the treatment of basilar apex, PCA, and superior cerebellar artery aneurysms which is the expanded endoscopic endonasal transclival approach [28]. Unfortunately, to our knowledge, there are no reports which compare the results of this approach with the classical microsurgical or endovascular techniques.…”
Section: Discussionmentioning
confidence: 99%